Science Links 9 : Worktext for Scientific and Technological Literacy - Aquino, Marites D.; Madriaga, Ph.D., Estrellita A.; Valdoz, Meliza P.; Biong, Jonna A. (Sampaloc, Manila : Rex Book Store, Inc., 2017)
"The Science Links (Revised Edition) series is a program that provides an interdisciplinary approach such as the social, historical, philosophical, technological, and problem-solving contexts in the teaching-learning process." It is designed to provide meaningful lessons to high school students who are dependent in science and technology as prime movers of information and productive living. This series, aims to acquaint the students with the physical sciences that will help them understand and explain natural phenomena and increase their awareness of the role of human beings in preserving, conserving, and protecting the environment. This series is also aligned with the DepEd K to 12 Science Curriculum Guide of December 2013. Each worktext in this series has four quarters. Each quarter is introduced by an illustration and background information to direct the students' focus on the subject matter.
Includes bibliographical references.
English text